TAN MALAKA: FILSAFAT REALISME KETIMURAN - salahuddin harahap (UIN Sumatera Utara, 2020)
Tan Malaka, is one of the Indonesian thinkers who seems to have quite a high concern for philosophy as stated in his fairly popular work MADILOG stands for